Chronic diseases in Nyeri, Kenya: a study of knowledge and perceptions - Michael A.T. Freiberg; Nelson O. Onyango; Stephanie J. Ashbaugh; Khanjan Mehta (PAGEPress Publications, 2016)
The burden of chronic, non-communicable disease such as diabetes, cardiovascular disease, and cancer is growing in many developing countries including Kenya. The use of community health workers is an important tool to improve the access to care and education in rural areas. This study aims to understand the knowledge and perceptions among the general population regarding three chronic diseases - diabetes, hypertension, and cancer - in Nyeri, Kenya. Standardized, open-ended interviews were conducted with 200 participants. This study shows that most individuals interviewed are familiar with these three diseases; however, knowledge varied among individuals with many having significant gaps in knowledge. These results are consistent with previous studies from this region and will inform future education directed at community health workers and the general population.